2022
DOI: 10.3389/fcdhc.2022.812134
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diabetes and Hyperglycemia on COVID-19 Infection Course—A Narrative Review

Abstract: It was previously reported that subjects with diabetes mellitus (DM) are more vulnerable to several bacterial or viral infections. In the era of coronavirus disease 2019 (COVID-19) pandemic, it is reasonable to wonder whether DM is a risk factor for COVID-19 infection, too. It is not yet clear whether DM increases the risk for contracting COVID-19 infection or not. However, patients with DM when infected are more likely to develop severe or even fatal COVID-19 disease course than patients without DM. Certain c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 216 publications
(354 reference statements)
0
5
0
Order By: Relevance
“…The risk of intensive care unit (ICU) admission and the poor short-term outcome were higher in COVID-19 patients with diabetes [6] , with twice the risk of COVID-19 mortality as non-diabetics [7] . Furthermore, patients with diabetes may experience prolonged symptoms or develop post-discharge complications such as post-COVID-19 syndrome [8] . This relationship between diabetes mellitus and COVID-19 infection may be bidirectional, as some studies have observed that diabetes may not only be a cause of poor COVID-19 prognosis, but COVID-19 may induce worsening hyperglycaemia and insulin resistance in return [8] .…”
Section: Introductionmentioning
confidence: 99%
“…The risk of intensive care unit (ICU) admission and the poor short-term outcome were higher in COVID-19 patients with diabetes [6] , with twice the risk of COVID-19 mortality as non-diabetics [7] . Furthermore, patients with diabetes may experience prolonged symptoms or develop post-discharge complications such as post-COVID-19 syndrome [8] . This relationship between diabetes mellitus and COVID-19 infection may be bidirectional, as some studies have observed that diabetes may not only be a cause of poor COVID-19 prognosis, but COVID-19 may induce worsening hyperglycaemia and insulin resistance in return [8] .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, DM is characterized by a chronic, proinflammatory state, so diabetic patients are more likely to develop a catastrophic inflammatory response to COVID-19 infection. Also, patients with DM often present multiple comorbidities, such as CVD, obesity, and metabolic syndrome, which may mediate the increased risk for complicated COVID-19 [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ACE2 receptor acts as a cellular entry mediator for SARS-CoV-2, which may render diabetic patients more vulnerable to the virus [ 13 , 14 ]. Hyperglycemia can induce glycosylation of ACE2 receptors, thereby increasing viral entry, independent of receptor expression [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…DM has also been associated with dysregulation of innate and adaptive immunity, caused by dysfunction of neutrophils, macrophages, and natural killer (NK) cells, as well as suppressed cytokine production [ 17 ]. Conversely, DM is linked to a chronic, pro-inflammatory state [ 15 , 18 ]. Therefore, individuals with DM are more susceptible to developing an exaggerated inflammatory response to SARS-CoV-2 infection [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation